Automatic movement segmentation in the upper limb functional assessment of children with cerebral palsy - Anaya Campos, L. E.; Quijano González, Y.; Quiñones Urióstegui, I.; Alessi Montero, A.; Bueyes Roiz, V.; Chong Quero, J. E. (Revista Mexicana de Ingenieria Biomedica, 2017)
Cerebral Palsy (CP) is a group of permanent pre, post and perinatal disorders of the motor and posture development due to non-progressive alterations in brain’s natural development caused by injuries in the Central Nervous System. Due to the importance of the daily use of the upper limb members, it’s important to consider more efficient ways to evaluate the performance in patients diagnosed with CP. One way to obtain an evaluation of the performance of the thoracic member is recording defined movements and calculating the smoothness, using an instrumented sorting block box. Our objective is to create a protocol of valuation for the upper member that is objective, efficient and that gives a quantitative feedback of the grade of the motor affectation of child with PC in a clinical environment.